Determination of Ethanol Content in Sticky Rice Tape with Varying Fermentation Time Using the GC-FID Method - Sari, Aisah Kensar Nawang Wulan; Ratnasari; Mumtazah, Dinung Zahra Vaqroh; Maya, Najwa Aifa Noor (Journal of Nutraceuticals and Herbal Medicine, 2025)
Sticky rice tape is one of the fermented products. The fermentation process of sticky rice tape involves the addition of microorganisms to make sticky rice into the desired product. The microorganisms commonly used are yeast. Yeast is a yeast that converts carbohydrates (starch) into sugar and alcohol. This study aimed to determine the ethanol content of the fermented sticky rice tape with a specific period, namely two days and five days. The research method used to analyze ethanol content is gas chromatography with a flame ionization detector. The average ethanol content in the two-day fermentation was 0.1008% b/b. The five-day fermentation was 0.188% b/b based on the standardized ethanol calibration curve equation y = 28.227x + 2.0768, with a correlation coefficient 0.99. These results showed that the longer the fermentation time, the higher the ethanol content.